1980
DOI: 10.1530/jrf.0.0580267
|View full text |Cite
|
Sign up to set email alerts
|

Sperm tail axoneme alterations in the Wobbler mouse

Abstract: In Wobbler mice (neurological mutants affected with progressive motor neurone degenerative disease) a defect in sperm tail mobility and axonemal geometry was observed. Similar but less extensive abnormalities were seen in the ciliary axonemes of the ductuli efferentes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 5 publications
2
20
0
Order By: Relevance
“…Among the best characterized of these are quaking (qk) (Sidman et al, 1964;Samorajski et al, 1970;Bennett et al, 1971), Purkinje cell degeneration (pcd) (Mullen et al, 1976;Handel and Dawson, 19811, and wobbler (wr) (Duchen and Strich, 1968;Leestma and Sepsenwol, 1980;Heimann et al, 1991). All of these mutations are autosomal recessive and all cause motor deficits as well as sterility in homozygous mutant mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the best characterized of these are quaking (qk) (Sidman et al, 1964;Samorajski et al, 1970;Bennett et al, 1971), Purkinje cell degeneration (pcd) (Mullen et al, 1976;Handel and Dawson, 19811, and wobbler (wr) (Duchen and Strich, 1968;Leestma and Sepsenwol, 1980;Heimann et al, 1991). All of these mutations are autosomal recessive and all cause motor deficits as well as sterility in homozygous mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…Among the phenotypes exhibited by these mutant mice are failure of spermatid elongation, abnormal tail formation, and abnormal acrosome development (Bennett et al, 1971;Mullen et al, 1976;Leestma and Sepsenwol, 1980;Handel and Dawson, 1981;Heimann et al, 1991). Although weauer also affects terminal differentiation of sperm, most of the features of the testicular phenotype are dissimilar to what is seen in qk, pcd, and wr mice.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been reported that the abnormal axoneme is induced by hereditary disease as in the Wobbler mouse and Kartagener's syndrome (LEESTMA and SEPSENWOL, 1980;AFZELIUS, 1981;AITKEN et al, 1983). Judging from extremely rare cases involving the abnormal axoneme, it is considered that the abnormal axoneme may be controlled by hereditary factors rather than other non-hereditary ones, while the periaxonemal components are controlled by other factors.…”
Section: Discussionmentioning
confidence: 99%
“…In certain t haplotypes and the Wobbler mutation (wr), sperm microtubules are also arranged in aberrant patterns in the vas deferens but appear to be normal in the testis (Dooher and Bennett 1977;Leestma and Sepsenwol 1980). The defective nature of these mutant sperm may become manifest in the epididymis because at this time they undergo dramatic changes in morphology and biochemistry and acquire motility (Hoskins and Vijayaraghavan 1990).…”
Section: Defective Sperm Motility and Axoneme Disruptionmentioning
confidence: 99%
“…The defective nature of these mutant sperm may become manifest in the epididymis because at this time they undergo dramatic changes in morphology and biochemistry and acquire motility (Hoskins and Vijayaraghavan 1990). Interestingly, sperm tail axonemes from both wr/ wr and sterile AE24 mice usually contain the same microtubule pattern (5 + 2) and are missing the same outer doublets (4--7) (Leestma and Sepsenwol 1980}. Mutations leading to sperm paralysis and male sterility have been described in humans as well as in mice (Ryder et al 1990}. The best described disease is immotile-cilia (Kartagener's) syndrome, in which men suffer from chronic sinobronchial infections and abnormal motility of both respiratory cilia and sperm flagella (Eliasson et al 1977).…”
Section: Defective Sperm Motility and Axoneme Disruptionmentioning
confidence: 99%